Analisis Ketahanan Web Application Firewall Terhadap Serangan SQL Injection - Humaira, Hana Nazla; Hadiana, Asep Id; Ashaury, Herdi (Peneliti.net, 2024)
The ever-advancing technological transformation has brought benefits to our daily lives. Thanks to these technological advances, it is very easy to get access to information, communicate with platforms, and conduct transactions in an increasingly sophisticated digital environment. Web application services are one of the positive impacts of the development of the digital world. However, behind the ease of access offered by web applications, it is often targeted by cyber criminals to obtain sensitive data within it. The application of Web Application Firewall (WAF) as a web application security from SQL injection attacks can be a solution to security issues. This research involves several different WAF solution selections. The results show that the effectiveness of WAF in protecting applications from SQL injection attacks varies depending on the type of attack. From the attacks performed, Naxsi was able to filter out 99% of the attacks and ModSecurity 100%.